Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) Prediction, Molecular Docking, and In Vitro Evaluation of Curcumin Against Escherichia coli Biofilm on Catheter Surfaces - Hasyrul Hamzah; Muhammad Aidil Fitrah; Sylvia Utami Tunjung Pratiwi; Sholahuddin Rhatomy; Asriullah Jabbar; Riza Maulana; Virgiawan Yoga Pratama (Environmental Analysis Health and Toxicology, 2026)
Catheter-associated urinary tract infections (CAUTIs) are often related to bacterial adhesion and biofilm formation on catheter surfaces, which may reduce the effectiveness of antimicrobial treatment. Curcumin has been reported to possess antimicrobial and antibiofilm properties; however, its activity against Escherichia coli biofilm biomass on catheter surfaces requires further evaluation. This study aimed to investigate the preliminary antibacterial and antibiofilm activity of curcumin against Escherichia coli ATCC 25922 using in vitro catheter-surface biofilm assays and in silico analysis. Absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction was performed using pkCSM, while molecular docking was conducted to evaluate possible ligand–target interactions. The in vitro assays evaluated OD595-based bacterial/adherent biomass reduction, mid-phase biofilm inhibition, maturation-phase biofilm inhibition, and preformed biofilm biomass reduction. Curcumin showed favorable predicted intestinal absorption and was not predicted to cause AMES toxicity, hepatotoxicity, or skin sensitization. Molecular docking suggested a possible interaction between curcumin and glutamine phosphoribosylpyrophosphate amidotransferase (1ECJ). Curcumin reduced OD595-based bacterial/adherent biomass by 73.15 ± 1.28% at 1% w/v and reduced mid-phase, maturation-phase, and preformed biofilm biomass by 68.32 ± 0.48%, 64.89 ± 1.95%, and 57.04 ± 1.75%, respectively. These findings suggest that curcumin may reduce E. coli biofilm biomass on catheter surfaces under the tested conditions. Further studies using well-characterized uropathogenic E. coli strains, clinical catheter-associated isolates, corrected raw OD values, viability-based assays, and physiologically relevant catheter models are required to validate its antibiofilm potential.